Identification of two subfamilies of micropia transposable element in species of the repleta group of Drosophila - de Almeida, L. M.; Carareto, CMA (Kluwer Academic Publ, 2004)
The occurrence, number of insertion sites and antisense RNA expression of micropia transposable element were studied in 26 species that belong to three subgroups (mercatorum, mulleri and hydei) of repleta group of Drosophila. Under high specific PCR, micropia sequences were detected in 11 species, but under less stringent condition, this retrotransposon was detected in all species. The widespread distribution of micropia suggests that this element was already present at the common ancestor of the repleta group of Drosophila. Southern blot analysis showed a variation from 0 to 17 different insertion sites and the occurrence of male-specific sequences. We found that the expression of the 1.0 kb micropia antisense RNA is variable among the species and tissues (soma and testis), which suggests that more than one mechanism regulates transposition in these species. Variation of amplification by PCR and of antisense RNA expression, as well as divergence of nucleotide sequences among the species allow us to suggest that at least two subfamilies of micropia transposable element are harbored by the genome of this species group.
Keywords: antisense RNA; Drosophila; micropia; micropia subfamilies; number of insertion sites; repleta group; retrotransposon